Clinical and epidemiological profile of congenital hyperinsulinism in Brazil - Liberatore Junior, Raphael D.; Marques, Anna L.; Dos Santos, Laura L.; Luciano, Thais M. (Frontiers in Endocrinology, 2025)
IntroductionCongenital hyperinsulinism is the most common cause of persistent hypoglycemia in children, often leading to severe neurological complications. Objective: This study aimed to describe the clinical and epidemiological profile of CHI in Brazil.MethodsA cross- sectional study was conducted with caregivers of CHI patients affiliated with the Associação do Hiperinsulinismo Congênito do Brasil. Data were collected via a structured questionnaire adapted from the HI Global Registry, covering clinical presentation, diagnostic pathways, genetic findings, and treatment strategies.ResultsCaregivers of 68 patients participated. Symptoms appeared before six months of age in 60% of cases, but 35.5% initially received incorrect diagnoses. Genetic testing was performed in 43 patients, but pathogenic variants were identified in only 7 cases, while the majority (31) was not aware of their results. Diazoxide was the most used medication, though 13% required pancreatectomy. Developmental delays were reported in 44% of cases.ConclusionsDelayed diagnosis and limited access to genetic testing and specialized treatments remain significant barriers in Brazil. This study underscores the need for improved awareness, early recognition strategies, and expanded access to genetic and therapeutic resources to optimize patient outcomes.